Synthesis, Characterization, and In Vivo Toxicological Evaluation of Copper (II) Oxide Containing Herbometallic Siddha Nanocomplex “Thamira Parpam” - Royapuram Parthasarathy, Parameswari; Manikandamathavan, Verasundaram M.; Chandronitha, Chandranayagam; Vasanthi, Hannah R.; Mohan, Vasanth Kumar; Vijayakumar, Venkataramanan; Shanmugam, Rajeshkumar; Sekaran, Saravanan; Unni Nair, Balachandran; Chamundeeswari, Duraipandian; Thyagarajan, Sadras Panchatcharam (Frontiers in Bioengineering and Biotechnology, 2022)
“Thamira parpam” (TP), a copper based herbo-metal oxide (copper (II) oxide) nanodrug has been used in siddha medicine for centuries owing to its anti-ulcerogenic property. However, the physicochemical properties and in vivo toxicity of TP still remains elusive. Rigorous clinical translation requires deciphering these vital properties. We have synthesized TP following a gold standard protocol in traditional siddha methodology. We assessed the size, phase, elemental constituents and thermal stability of TP by SEM and TEM, XRD, EPR and EDAX analyses respectively. The results depicted the conversion of metallic copper into Copper (II) oxide in the final stages TP preparation and exhibited nano dimensions ranging between 10-50 nm. The XPS spectra revealed the presence of oxygen deficient state and a carbonaceous coating was found on the surface of TP by TEM analysis. In vivo safety was studied in rat toxicity models by adopting OECD guidelines. Body weight changes, feed and water intake were unaltered upon TP administration. Hematological, biochemical profiling and histopathological findings also suggested its non-toxic nature with no abnormalities in major organs and its functions. Interestingly, we found that the metal toxicity could have been subdued because of the carbonaceous coating around the nanoparticle copper (II) oxide confirming that the drug is safe at low dose. Overall, our study has enlightened the safety of TP supporting the use of siddha formulations.